2017
DOI: 10.1002/pssa.201700323
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of InGaN/GaN Multiple‐Quantum‐Well Solar Cells Grown on Sapphire and AlN Template by Metalorganic Chemical Vapor Deposition

Abstract: Two kinds of substrates, sapphire and AlN/sapphire template (AlN template), are used for the growth of InGaN/GaN multi‐quantum‐well solar cell structures by metalorganic chemical vapor deposition, and their material and device properties are investigated. The results show that the samples grown on AlN template have a better crystal quality with a larger in‐plane compressive strain than those on sapphire, and solar cells fabricated on sapphire mostly exhibit better performance than those on AlN template. An ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Advancements in growth techniques made it possible to achieve highly improved optoelectronic device performance through high-quality single-crystal material growth [391][392][393] . Since GaN exhibits a smaller degree of lattice mismatch with the lattice of AlN compared with that of sapphire (a = 4.7576 Å and c = 12.9834 Å at 25 °C) [293] , the epitaxial growth of GaN films on AlN/sapphire templates can be conveniently carried out [394,395] . This assisted in the reduction of dislocations on overgrown active regions.…”
Section: Innovative Materials Growth Mechanisms and Device Fabrication Techniquesmentioning
confidence: 99%
“…Advancements in growth techniques made it possible to achieve highly improved optoelectronic device performance through high-quality single-crystal material growth [391][392][393] . Since GaN exhibits a smaller degree of lattice mismatch with the lattice of AlN compared with that of sapphire (a = 4.7576 Å and c = 12.9834 Å at 25 °C) [293] , the epitaxial growth of GaN films on AlN/sapphire templates can be conveniently carried out [394,395] . This assisted in the reduction of dislocations on overgrown active regions.…”
Section: Innovative Materials Growth Mechanisms and Device Fabrication Techniquesmentioning
confidence: 99%
“…However, Miyoshi et al . demonstrated that the InGaN/GaN MQWs grown on AlN/sapphire template has a larger in-plane compressive strain than those grown on LT-GaN/sapphire template 33 . The larger in-plane compressive strain in the InGaN QWs would induce a larger piezoelectric polarization electric field, resulting in a more severe QCSE for LED on sputtered AlN/sapphire template.…”
Section: Introductionmentioning
confidence: 99%